Development of the Composition and Technology of a Granular Dosage form Based on a Thick Milk Thistle Extract and Ademetionine - D. I. Pisarev; O. O. Novikov; E. T. Zhilyakova; N. N. Boyko; R. A. Abramovich; O. G. Potanina; S. Lazar; A. Sayed Ahmad; R. Nasser (Разработка и регистрация лекарственных средств)
Introduction. The creation of rational combined medicines with hepatoprotective activity is an urgent task of medicinal science. Ademetionin shows pharmacological effectiveness in cytolysis, cholestasis, synthetic insufficiency. Silybin, in turn, is effective in cytolysis, synthetic insufficiency, mesenchymal inflammation, fibrosis and pathological regeneration. Thus, the combination of these substances covers almost the entire set of clinical and morphological syndromes of liver damage and has a wide range of effects in various liver pathologies.Aim. The purpose of this study was to develop a combined granular dosage form containing a thick extract of milk thistle, ademetionin and analytical support for this process.Materials and methods. To obtain a thick extract from the fruits of Silybum marianum L. a traditional percolation method was used in a battery of 3 diffusers. Extractant removal was performed using a rotary evaporator IR-1M3 under vacuum. For the analysis of silybin in the obtained thick extract from the fruit of S. marianum L. the method of HPLC was used. Validation evaluation of the method was performed according to generally accepted parameters.Results and discussion. A modular combined dosage form based on a thick extract of S. marianum L. and ademethionine was developed. Lactose was introduced as an auxiliary agent. The quality of pellets was evaluated according to generally accepted criteria. The validation parameters of the manufactured dosage form were determined using the HPLC method. Accuracy and precision were determined by the method of additives in a series of 9 experimental samples of granules. The results of determining the linearity, precision and correctness of the method for determining silybin and ademetionin in a combined model drug form showed correct results.Conclusion.Thus, a combined granular dosage form containing a thick extract of milk thistle, ademetionin, has been developed. Analytical support of this process using the HPLC method was performed. Validation studies of the developed methodology were carried out. The field of application of the obtained results is practical pharmacy. Further research should concern the conduct of a set of pharmacological tests.